1992
DOI: 10.1227/00006123-199206000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Essential Hypertension Associated with Neurovascular Compression

Abstract: According to the hypothesis of Jannetta, an arterial compression of the left root entry zone (REZ) of cranial nerves IX and X by looping arteries could play an important role in the pathogenesis of essential hypertension. In an initial anatomical study, the positions of the left vagus and glossopharyngeal nerves in the skull were radiographically determined in 10 cadavers. By using a pattern of REZ topography developed from this information, the angiographic findings in 107 hypertensive and 100 normotensive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…In the current study, 71% of patients with NC on the left or both sides had hypertension, a finding similar to that reported previously [3, 9, 18]. Further research is necessary to determine whether normotensive patients with NC are more likely to develop an increased arterial pressure in the future.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the current study, 71% of patients with NC on the left or both sides had hypertension, a finding similar to that reported previously [3, 9, 18]. Further research is necessary to determine whether normotensive patients with NC are more likely to develop an increased arterial pressure in the future.…”
Section: Discussionsupporting
confidence: 88%
“…Several clinical studies have indicated a causal relationship between hypertension and NC of the ventrolateral medulla on the left but not on the right side [9, 10, 11, 13, 18]. Our results also demonstrated that patients with left-side NC were more frequently hypertensive as compared with patients with NC on the right side.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The pathogenesis of neurogenic HTN is mainly related to the overactivity of the sympathetic nervous system (5,6). Several studies have shown that neurogenic HTN usually refers to HTN caused by vascular compression of the RVLM and the REZ of the IX and X cranial nerves (7)(8)(9)(10)(11)(12). Most hypertensive patients can achieve ideal blood pressure control with systematic and regular medication.…”
Section: Introductionmentioning
confidence: 99%
“…The association between pulsatile arterial compression (AC) of the ROS and essential hypertension (EHTN) in humans has been the subject of numerous studies [13][14][15][16][17][18][19][20][21][22][23][24]. However, inconsistencies have existed in the results, as well as the exact location and laterality of arterial contact.…”
Section: Introductionmentioning
confidence: 99%